Benefits of Gotu Kola Leaf in Responding to Prevent The Form of Keloid in The Wound - Muhammad Bagus Nitei Ago; Diki Prawira Adifa (GLOBAL HEALTH SCIENCE GROUP, 2020)
Keloids are a type of scar, which is the result of overgrowth of dense fibrous tissue that usually develops after healing a skin injury. Keloids occur due to prolonged inflammatory phases in the wound, resulting in increased fibroblast activity and continuous extracellular matrix formation. Gotu kola (Centella asiatica) leaves are effective in the treatment of wounds because they contain Triterpene components such as asiatic acid, madecassic acid, asiaticoside and madecassoside. The purpose of this literature review is to report the latest scientific findings on the role of gotu kola leaf content in preventing keloid formation by increasing fibroblast proliferation, increasing collagen synthesis and mucopolysaccharide acids, increasing intracellular fibronectin which then significantly increases the tensile strength of newly formed skin, inhibiting the phases of the formation of skin, inflammation of the keloid scar tissue. The method used in this article is article search through the NCBI database and Google Scholar. The year of publication of library resources is from 1999 to 2018 with 20 sources of literature. The theme collected was related to the Centella asiatica leaf content towards the wound phase to prevent keloid formation. The results of the synthesis of articles that have been found are gotu kola leaves can inhibit the formation of keloids in wounds. Keywords: gotu kola leaf, keloid, wound